2011
DOI: 10.4321/s1130-01082011001200004
|View full text |Cite
|
Sign up to set email alerts
|

Standard criteria versus Rosemont classification for EUS-diagnosis of chronic pancreatitis

Abstract: Aim: to study the possible differences in the final diagnosis of chronic pancreatitis by using standard classification described by Wiersema et al. and the new classification proposed recently by Rosemont.Material and methods: forty-seven patients with the diagnosis of chronic pancreatitis were included in this study. The parenchymal and ductal criteria were studied, the patients were divided in two groups for Wiersema criteria: < 4 criteria, non-diagnostic for chronic pancreatitis and ≥ 4 criteria, diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
0
6
0
4
Order By: Relevance
“…Several studies on the accuracy of EUS criteria for the diagnosis of CP have been reported 27–30 . The higher the number of detected criteria is, the higher is the specificity and positive predictive value of the EUS finding.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on the accuracy of EUS criteria for the diagnosis of CP have been reported 27–30 . The higher the number of detected criteria is, the higher is the specificity and positive predictive value of the EUS finding.…”
Section: Discussionmentioning
confidence: 99%
“…The EUS was performed by an expert endoscopist. The Rosemont criteria were used for diagnosis of chronic pancreatitis …”
Section: Methodsmentioning
confidence: 99%
“…The Rosemont criteria were used for diagnosis of chronic pancreatitis. 15 Statistical analyses. A priori, we calculated a sample of 50 individuals will limit the width of the 95% confidence interval to ± 5% if the estimated prevalence of PEI (H1) and chronic pancreatitis (H3) are both 10%.…”
Section: Methodsmentioning
confidence: 99%
“…2,3 La ultrasonografía endoscópica (USE) es en la actualidad el método de elección para la detección de cambios morfológicos tempranos relacionados a PC, debido a su capacidad para detectar cambios menores parenquimatosos y ductales, que no pueden ser detectados por otros métodos de imágenes, y su especificidad aumenta con el aumento de los criterios diagnósticos. 4 Para el diagnóstico por USE de PC, los criterios de Rosemont modificados son los más utilizados. La clasificación de Rosemont se compone de criterios mayores y menores bien definidos y cuatro grupos de diagnóstico.…”
Section: Introductionunclassified